Implementation of Blom’s key predistribution scheme by using elliptic curve cryptography / Md Nizam Udin ... [et al.] - Udin, Md Nizam; Mohd Amin, Farah Azaliney; Abdul Malek, Aminah; Zulkifili, Nur Annisa; Ghazali, Nur Atiqah; Mohd Ridzuwan, Siti Aisyah (Penerbit UiTM, 2021)
Cryptography, along with its various methods is used to serve the security communication purpose. Cryptography is said to be secure if the encryption key is hard to break by the attacker. Initially, Blom’s Key pre-distribution uses an integer finite field which makes this scheme easy to be intervened by attackers and criminal activists. Hence, this study suggests implementing the Elliptic Curve Cryptography to better enhance the security of the original Blom’s. In this proposed scheme, points generated from the elliptic curve will be appointed as public identifiers to be used in the original scheme. The private key and session key of each user are generated using the addition law mathematical operation with public identifiers assigned. Two users who intend to communicate with each other will obtain a common session key. Overall, the modification of Blom’s Key pre-distribution scheme will be presented in this study.